The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1093/bjs/znac324
|View full text |Cite
|
Sign up to set email alerts
|

Transanal versus laparoscopic total mesorectal excision for mid and low rectal cancer (Ta-LaTME study): multicentre, randomized, open-label trial

Abstract: Background Transanal total mesorectal excision (TaTME) is a minimally invasive surgical technique that tries to avoid conversion to open surgery. However, specific intraoperative complications and local recurrences have cast some doubt on the suitability of the technique. The primary endpoint of the present study was a composite outcome of conversion surgery. Secondary objectives were to assess postoperative recovery, and pathological and oncological outcomes. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…At a median follow-up of 39 months, this trial reported LR rates of 6.1% in the l-TME group and 1.8% in the taTME group ( p = 0.3). 111 Both of the above-mentioned trials reported similar pathologic outcomes between l-TME and taTME, including status of the distal and circumferential resection margins and completeness of the mesorectal specimen. 111 None of these procedures resulted in CO 2 embolism or urethral injury.…”
Section: Certainty Of Evidencementioning
confidence: 88%
“…At a median follow-up of 39 months, this trial reported LR rates of 6.1% in the l-TME group and 1.8% in the taTME group ( p = 0.3). 111 Both of the above-mentioned trials reported similar pathologic outcomes between l-TME and taTME, including status of the distal and circumferential resection margins and completeness of the mesorectal specimen. 111 None of these procedures resulted in CO 2 embolism or urethral injury.…”
Section: Certainty Of Evidencementioning
confidence: 88%
“…The incidence of anastomotic leakage in transabdominal and transanal rectal cancer surgery remains controversial 28,29 . We performed subgroup analysis based on different surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…In the first 2 RCTs published to date comparing outcomes of laparoscopic versus taTME in sphincter-saving LAR for rectal cancer, the rate of IC TME was 0% in both trials’ taTME arms, totaling 599 patients. The wide-ranging variation in reported rates of IC TME raises questions regarding QC measures used to validate the assessment of TME grade in prospective observational and randomized trials 30,31 . Liu et al 30 acknowledged that despite an independent review by an oversight committee, an over-estimation bias for successful resection, based on the TME grading assessed by pathologists at each of the 16 participating institutions, still remains a “certain possibility.” Among 13 prospective and randomized rectal cancer surgical trials published or ongoing, only 7 described pathology QC measures to validate the accuracy of TME specimen grading, (Supplemental File 5, http://links.lww.com/SLA/E739).…”
Section: Discussionmentioning
confidence: 99%
“…Large taTME series and registries report CRM-positive rates ranging from 1.4% to 12.7% 21–25 and rates of IC TME ranging from 1.5% to 11% 24,26–29 . In the first 2 RCTs comparing laparoscopic to taTME, CRM-positive rates varied from 0% to 2.4% with IC TME reported in 0% to 22% 30,31 . The variability in mesorectal grade reported in RCTs raises questions regarding the internal validity of reported TME grades and whether quality control (QC) measures should be systematically implemented in the assessment of this key pathologic endpoint 30,32 .…”
mentioning
confidence: 99%
See 1 more Smart Citation